2016
DOI: 10.1111/febs.13725
|View full text |Cite
|
Sign up to set email alerts
|

A new cryptic cationic antimicrobial peptide from human apolipoprotein E with antibacterial activity and immunomodulatory effects on human cells

Abstract: Cationic antimicrobial peptides (AMPs) possess fast and broad-spectrum activity against both Gram-negative and Gram-positive bacteria, as well as fungi. It has become increasingly evident that many AMPs, including those that derive from fragments of host proteins, are multifunctional and able to mediate various immunomodulatory functions and angiogenesis. Among these, synthetic apolipoprotein-derived peptides are safe and well tolerated in humans and have emerged as promising candidates in the treatment of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 64 publications
2
81
0
Order By: Relevance
“…Other reports, focused on monomeric and dimeric synthetic peptides encompassing ApoE amino acids 130 to 169, revealed the importance of α‐helical conformations and of positively charged amino acids . Several recent reports are focused on the study of ApoE‐derived peptide antimicrobial and immunomodulatory properties . They have been identified in the receptor binding region, or they have been obtained by combining clusters of residues identified in the same region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports, focused on monomeric and dimeric synthetic peptides encompassing ApoE amino acids 130 to 169, revealed the importance of α‐helical conformations and of positively charged amino acids . Several recent reports are focused on the study of ApoE‐derived peptide antimicrobial and immunomodulatory properties . They have been identified in the receptor binding region, or they have been obtained by combining clusters of residues identified in the same region.…”
Section: Introductionmentioning
confidence: 99%
“…The method assigns an antimicrobial score to peptides based on their net charge, hydrophobicity and length, and 2 bacterial strain‐dependent weight factors . By means of this method, we have already reported the characterization of novel human peptides including an exhaustive structural and functional study of a cryptic peptide identified in human ApoE (residues 133‐150) . We deeply characterized the ability of ApoE (133‐150) to assume stable conformations in the presence of membrane mimicking agents and LPS as well as its antibacterial and immunomodulatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of apoE4 fragment 1–272 induced its binding to various components of mitochondrial complexes and promoted mitochondrial dysfunction in Neuro-2a cells [82]. On the other hand, apoE 133–149 peptide displayed neuroprotective functions, besides its anti-inflammatory properties [83].…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…ApoE 133–150 peptide was found to be lethal for several Gram-positive ( Staphylococcus aureus , Bacillus subtilis ) and Gram-negative ( Pseudomonas aeruginosa , Escherichia coli , Klebsiella pneumoniae ) bacteria, but displayed no toxicity on several human cell cultures [83]. Furthermore, this peptide reduced the expression of pro-inflammatory cytokines in LPS-treated THP-1 macrophages.…”
Section: Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation